2009
DOI: 10.1007/s00335-009-9178-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide screening for genetic loci associated with noise-induced hearing loss

Abstract: Noise-induced hearing loss (NIHL) is one of the more common sources of environmentally induced hearing loss in adults. In a mouse model, Castaneous (CAST/Ei) is an inbred strain that is resistant to NIHL, while the C57BL/6J strain is susceptible. We have used the genome-tagged mice (GTM) library of congenic strains, carrying defined segments of the CAST/Ei genome introgressed onto the C57BL/6J background, to search for loci modifying the noise-induced damage seen in the C57BL/6J strain. NIHL was induced by exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 16 publications
0
23
0
1
Order By: Relevance
“…The OBN noise exposure was previously described [White et al, 2009]. During exposure, mice were housed in a circular ¼ inch wire-mesh exposure cage with four pie shaped compartments and were permitted to move about within the compartment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OBN noise exposure was previously described [White et al, 2009]. During exposure, mice were housed in a circular ¼ inch wire-mesh exposure cage with four pie shaped compartments and were permitted to move about within the compartment.…”
Section: Methodsmentioning
confidence: 99%
“…We are able to exploit the evidence that there are genetic and environmental factors influencing ARHI and NIHL [Friedman et al, 2009; White et al, 2009]. Recently, genome wide association studies (GWAS) have been employed to discover genes conferring susceptibility to complex traits in humans.…”
Section: Introductionmentioning
confidence: 99%
“…A number of genetic loci have been identified that modulate the rate of hearing loss or the sensitivity to noise (White et al, 2009) and several that modulate both age and noise effects (Ohlemiller, 2006), suggesting common genetic features underlying each form of pathology. A complication in interpreting most previous genetic studies, however, is their reliance on inbred mouse strains, each of which consists entirely of individuals of a single genotype, and in which all loci have been forced to homozygosity.…”
Section: Introductionmentioning
confidence: 99%
“…Strains with PTS<20 at all frequencies were considered noise-resistant, whereas strains with PTS ≥20 at any frequency were considered noise-sensitive. A cutoff of 20dB was determined based on usage by prior studies [14,15]. Noise-sensitivities at each frequency were further categorized as mild (20≤PTS<30dB), moderate (30≤PTS<40dB), or severe (≥40dB).…”
Section: Methodsmentioning
confidence: 99%